Value of Private Lands Managed for Wild Northern Bobwhites in the Deep South - William E. Palmer; Shane D. Wellendorf; D. Clay Sisson; B. Bostick (National Quail Symposium Proceedings, 2017)
Successful northern bobwhite (Colinus virginiaus) management creating huntable bobwhite populations in the southeastern United States is largely practiced on private lands. These properties not only support high density bobwhite populations, they also support biodiversity including many declining or endangered species associated with frequently-burned pine savannas. The private land model has proven sustainable over centuries and has recently increased with >20,000 ha of wild bobwhite lands added in Georgia, Florida, and South Carolina since 2000. The NBCI recognizes private lands are critical to restoration of bobwhites but, despite their conservation value, no studies have quantified areas under wild bobwhite management. We mapped 259 properties totaling ~ 345,614 ha with wild bobwhite management principally in Georgia, Florida, Alabama, and South Carolina, and are completing mapping in Mississippi, Virginia, and North Carolina. Our survey data found management actions were consistent across these properties including maintaining open pine canopy, reducing hardwoods in upland areas, prescribed ﬁre on areas of appropriate sizes and distribution, year- round supplemental feeding, nest predator management, and conservative harvest rates. Adoption of these management practices are a result of long-term research demonstrating their efﬁcacy. Density of bobwhites on a property was related to landscape composition with lower densities on more fragmented sites. Properties in core areas surrounded by other managed properties often achieved bobwhite densities of 5–8 quail/ha. Bobwhite densities on smaller isolated properties densities were ~ 2.5 quail/ha during fall. Aspects of this successful management model may be useful to other private lands as well as public management areas focused on northern bobwhite.
Keywords: Colinus virginianus; NBCI; northern bobwhite; private land management; southeastern United States